Originalitas Pemikiran Fonetik Al-Khalil Ibn Ahmad Al-Farahidi - Akhmad Saehudin (Jurusan Bahasa dan Sastra Arab Fakultas Ushuluddin dan Adab UIN Sultan Maulana Hasanuddin Banten, 2014)
As a pioneer of Arabic phonetic scholar and a founder of Arabic linguistic and literature sciences, al-Khalîl is the master teacher for linguists after him. Nevertheless, the wind of skepticism upon the his linguistic thoughts, after it was firstly blown by some Orientalists, has been responded by some Arabian scholars by following their lines. The central discourse, which this article tries to deal with, is whether his linguistic thoughts were really his own? Being supposed to be the origins of al-Khalîl’s thoughts, Indians and Greeks have had the linguistic thoughts which are to be studied in this article by comparing them with those of al-Khalîl. The writer finds that the skepticism upon al-Khalîl’s linguistic thoughts can not be proved. Al-Khalîl has had his own thoughts which were not originated from neither India nor Greece.